Timing of maternal death: Levels, trends, and ecological correlates using sibling data from 34 sub-Saharan African countries - Merdad, Leena (PLoS One, 2018)
Millennium Development Goal 5 has not been universally achieved, particularly in sub-Saharan Africa. Understanding whether maternal deaths occur during pregnancy, childbirth, or puerperium is important to effectively plan maternal health programs and allocate resources. Our main research objectives are to (1) describe the proportions and rates of mortality for the antepartum, intrapartum, and postpartum periods; (2) document how these trends vary by sub-region; and (3) investigate ecological correlations between these rates and maternal care interventions. We used data from the Demographic and Health Survey program, which comprises 84 surveys from 34 sub-Saharan African countries conducted between 1990 and 2014. We calculated age-standardized maternal mortality rates and time-specific maternal mortality rates and proportions, and we assessed correlations with maternal care coverage. We found high levels of maternal mortality in all three periods. Time-specific maternal mortality rates varied by country and region, with some showing an orderly decline in all three periods and others exhibiting alarming increases in antepartum and postpartum mortality. Ecological analysis showed that antenatal care coverage was significantly associated with low antepartum mortality, whereas the presence of a skilled attendant at childbirth was significantly associated with low postpartum mortality. In sub-Saharan Africa, maternal deaths occur at high rates in all three risk periods, and vary substantially by country and region. The provision of maternal care is a predictor of time-specific maternal mortality. These results confirm the need for country-specific interventions during the continuum of care to achieve the global commitment to eliminating preventable maternal mortality.